A prospective double-blinded randomized controlled trial of the efficacy of haruan (channa striatus) spray on clean wounds - Lah, Nik Amin Sahid Nik (2017)
Background Channa striatus (Haruan), a fresh water fish indigenous to many tropical countries have long been regarded as valuable food fish in the Far East. Several studies showed, the Haruan did contain all the essential amino acids and fatty acids uniquely capable of accelerating the wound healing and it has anti-nociceptive effect. However so far no human study been done to assess the effectiveness of Channa striatus in wound healing. A prospective randomize controlled trial has been conducted on the effect of Channa striatus Spray versus placebo on clean wound to assess its pain control effect and cosmetic outcome. Methodology Hundred and two patients (102) underwent clean elective surgery; post-operatively they are randomized into two group. One group received Channa striatus Extract spray (n=51) another group receive placebo (n=51) on daily basis for 2 week. Then they were follow up on 2nd, 4th and 6th week to assess the pain control effect based on Visual Analog Pain Score (VAPS) and cosmetic outcome based on Visual Analogue Cosmetic Scale (VACS), Wound Evaluation Scale(WES) and Vancouver Scar Scale (VSS). Result The patient treated with Channa striatus spray displayed a better outcome in term of pain control compared to placebo. During analysis using repeated measure ANOVA, there was significant difference of patient’s pain score based on VAPS between Channa striatus spray and placebo (F-stat(df) = 4.80 (2), p-value = 0.010). In term of cosmetic outcome it showed a consistent significant better result in haruan spray group for all the 3 scoring system which is VACS, (F-stat(df) = 2.68 (2) , p-value <0.001), WES (F-stat(df) = 3.09 (2), p-value = 0.048). and VSS , F-stat(df) = 1.72 (2) , p-value = 0.011). Conclusion Our study suggest that application of Haruan Extract spray on clean wound has shown a significant better pain score result and cosmetic outcome on week 2, week 4 and week 6 comparatively with placebo